Iron Annie - Cassidy, Luke (Vintage crime/Black Lizard., 2022)
"Dundalk-The Town, to locals-took Aoife in when she left home at eighteen. Now she's gone from small time slinger of hash to a bona fide part of the crew that runs Dundalk's less legal enterprises. So when she's approached by the Rat King, a trusted associate, and asked to off-load a shipment of coke, she knows she can handle the job. The only issue is Aoife's girlfriend, Annie. The Rat King doesn't trust Annie, but Aoife doesn't trust herself to do the job without Annie catching wind. And then she lands on an idea. Annie has contacts in the UK, and sure it'd be better to get the coke as far away from Dundalk as possible. So Aoife and Annie get on a ferry and leave Ireland behind. At first, everything goes to plan. But then Annie starts talking about partnering up with a Scot she meets on a night out, and Aoife finds herself torn between the woman she loves and her loyalty to The Town"--